The role of Emotional Intelligence in health care professionals burnout. (13th November 2019) - Arnone, R; Cascio, M I; Parenti, I
Abstract: : The purpose of this study is to explore the relationship between Emotional Intelligence (EI) and burnout in health care professionals. More specifically, this survey has the purpose of demonstrating the role of EI as a protective factor against the risk of burnout. Health professionals (doctors, nurses, and other caregivers) composed the sample. Health care professionals were invited to complete the following tests: Self Report Emotional Intelligence Test (Schutte et al., 1998; it. ad. Craparo, et al.[35]); Link Burnout Questionnaire, LBQ; Other variables, such as gender, lenght of service (years of professional experience) and organizational department. Major results of this survey underline the relationship between EI and burnout. More specifically, there is a negative and significant correlation between burnout and Emotional Intelligence. Moreover, burnout varies depending on length of service: burnout increases between 5 and 10 years of experience and decreases over 10 years. Indeed, burnout is differently expressed amongst healthcare professionals: more specifically, Psycho-physical exhaustion, Detriment of the relationships and Burnout (total score) impact physician (doctors) more than other investigated health professionals. These findings seem to suggest the opportunity to improve Emotional Intelligence abilities through specific training programs, useful to promote the ability to cope with stress and to enrich the relationships in the workplace. Key messages: Burnout is more diffuse among health professionals working in emergency departments. Emotional intelligence has the role to cope with burnout.